Internet of Things Experiment Device for Laboratory Activities in Heat Transfer Mechanism - Siti Nur Rahmawati; Daru Wahyuningsih (Program Studi Teknik Komputer, 2025)
As a branch of fundamental science, physics studies the laws underlying physical events that happen in nature. To learn physics, laboratory activity is necessarily involved, and it requires supporting devices to observe and study phenomena that are physically abstract, such as heat transfer mechanisms. This research aims to develop an Internet of Things (IoT) experiment device for heat transfer using NodeMCU and describe its working principle and measurement result. It involved NodeMCU, MAX6675 sensor, and LCD 1602 as the main components. The procedures carried out in this research included planning, developing, testing, data collecting, data analyzing, and reporting. Multiple measurements were carried out to analyze the standard error value of the device. The standard error values of both thermocouples used in the device were 1,336104 for the first thermocouple and 0,754315 for the second. Additionally, the IoT device’s thermocouple readings were calibrated using the linear regression method and the validation experiment showed that the calibration has increased its accuracy value.